EFFECT OF TEMPERATURE ON THE FLUORESCENCE QUENCHING OF BIOLOGICALLY ACTIVE CARBOXAMIDE : Life Science-Spectroscopy - N.R. PATIL; R. M. MELAVANKI; H.D. PATIL; D. NAGARAJA; F. M. SANNINGANNAVAR (International Journal of Life Science and Pharma Research, 2013)
Fluorescence quenching of biologically active carboxamide namely (E)-2-(4-Chlorobenzylideneamino)-N (2- chlorophenyl) 4,5 6,7-tetrahydrobenzo[b]thiophene-3- carboxamide [ECNCTTC] by aniline and carbon tetrachloride has been carried out at room temperature (298 K) to understand the role of quenching mechanisms. The study has been carried out by both steady state in different solvents and by time resolved method in nheptane and cyclohexane. The Stern–Volmer plot has been found to be linear for all the solvents studied. The probability of quenching per encounter ‘p’ is determined in all the solvents and is found to be less than unity. It is found that, the activation energy Ea (E’a) is greater than the activation energy of diffusion, Ed. The results obtained by the transient method infer that the thermally assisted intersystem crossing, a non-radiative deactivation process from S1 to T2 is responsible for observed decrease in quantum yield and lifetime. Hence, from both the methods it can be concluded that quenching mechanism is not solely due to the material diffusion, but there is also contribution from the activation energy.